Is Serum Human Epididymis Protein HE4, More Specific than Cancer Antigen 125 in Patients with Benign Gynecological Diseases? - Sonia Aziz, Sahar Salahuddin Amir, Ihsanullah, Hina Shams, Umair Amir Khan, Saba Shams (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The cancer antigen 125 “CA125” and Human Epididymis protein 4 “HE4” are among some well worked out markers for recognition of malignancy in ovarian tumors. Their different cutoffs are determined and reported by various studies and mostly used recommended cutoffs are 35.0 U/mL for CA125 and 140pmol/L for HE4. They are both reported to recognize the malignancy well, but how specific they are for benign gynecological diseases is still needed to be worked out. Aim: To determine and compare the performance of CA125 and HE4 for benign gynecological pathologies. Methodology: A cross-sectional study was performed at Gajju Khan Medical College in collaboration with Armed forces Institute of pathology (AFIP). A total of 76 women of age above 18 years age, with benign ovarian pathology, confirmed through histological evaluation were enrolled. All these were examined on both markers, i.e. CA125 and HE4. Standard cutoffs of CA125 >35.0 U/mL and HE4>140 pmol/L were used to see if the case was labeled malignant, incorrectly. SPSS 20.0 was used to manage and analyze the data. Performance of the two markers were compared by using some descriptive analysis and using chi-square test. P-value ≤0.05 was considered significant. Results: The median age of these women was 40 years ranging between 18 and 71. Majority (86.8%) was premenopausal, The CA125 had no difference between pre and post-menopausal women but HE4 had a significant difference with p-value 0.029. there were 10.5% incorrect labeling of malignancy when evaluated for CA125, while only 2.6% incorrect on HE4. This difference was found statistically significant between two markers with p-value 0.05. Conclusion: HE4 is better and more specific marker for benign gynecological pathologies as compared to CA125 Keywords:Benign Ovarian Epithelial, Human epididymisprotein (HE4), Cancer Antigen 125 (CA125), Specificity